PENGARUH EDUKASI BANTUAN HIDUP DASAR DENGAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN KELOMPOK NELAYAN AILI STAR KECAMATAN BEO KABUPATEN KEPULAUAN TALAUD - Marlyn A. Pondete; Olvin Manengkey; Maryani Terine (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Providing Basic Life Support (BHD) is an intervention that can be provided by lay people or trained health workers to help those experiencing cardiac arrest, respiratory failure or airway obstruction. Basic Life Support is the first step to help and improve the function of important organs and is an important action for drowning victims who experience respiratory and cardiac arrest (respiration and circulation). The research objective is to determine the effect of basic life support education using audio-visual media on the knowledge of the Aili Star fishermen group in Beo District, Talaud Islands Regency. This research is a research method, namely Quasi Experimental. This research uses a one group pre test-post test design approach. The research was carried out in June 2024 in Beo District, Talaud Islands Regency. The population in this study was the families of all the Aili Star fishermen groups in Beo District, Talaud Islands Regency, totaling 16 people. The sample used a total population of 16 respondents. The statistical test used was the paried t-test with a significance level of 95% (α < 0.05). The results obtained were that the fishermen's knowledge before being given basic life support education with audio visual media, most of the fishermen had poor knowledge, namely as many as 11 repondents (31.3%) and after being given education, most of the fishermen had good knowledge, namely as many as 16 repondents (100%). The results of the statistical test with paired t-test showed that the p value was 0.000 or less than the α value of 0.05, so there was a significant increase in knowledge before and after providing basic life support education with audio-visual media.The conclusion of the results of the study is that there is an influence of basic life support education with audio visual media on the knowledge of the Aili Star fishermen group, Beo District, Talaud Islands Regency. Suggestions for the public to increase knowledge about the importance of first aid in accidents, especially drowning cases by seeking information from various sources